ECOLOGICAL CONDITIONS OF A TEMPORARY WETLAND IN BANGLADESH - Nazrul-Islam, A. K.M.; Khan, Fahmida; Khatun, Ambia; Khan, M. R.; Abdullah, A. N.M.; Jha, P. K. (Ecoprint: An International Journal of Ecology, 2013)
Investigation has been done to gain evidence on certain chemical properties of water and vegetation in area representative of the various wetland habitats which go under water during rainy season. The measurements were done with edaphic condition, water chemistry, and floristic composition. Water was neutral to alkaline and pH varied from 6.97 to 7.20 and conductivity was in the range of 97.5 m mhos to 240 m mhos. Seasonal variation of chloride content was observed throughout the year and the highest chloride (104.96 mg/l) was in the month of October. Dissolved oxygen concentration was very low (2.99 mg/l) in the month of October. With the decrease of water, the value of alkalinity became double (76.0 mg/). No distinct variation in the content of hardness was observed in the three different locations. Temporary hardness varied from 0.1 0 to 0.56 mg/l. High value of total solids in the month of July (70 mg/l) indicated that high amount of sediment are coming with the flow of water from upstream. Total suspended solids were higher than dissolved solids. Exchangeable cations were low in the beginning and an increasing tendency of Na and Ca was observed in the later stages of marsh formation. DOI: http://dx.doi.org/10.3126/eco.v18i0.9413 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: 71-76 Uploaded date: 12/22/2013